Investigation of the electrocaloric effect in a PbMg2/3Nb1/3O3-PbTiO3 relaxor thin film - Correia, T. M.; Young, J. S.; Whatmore, Roger W.; Scott, J. F.; Mathur, N. D.; Zhang, Qi (American Institute of Physics (AIP), 2009)
Permittivity measurements of a 0.93PMN-0.07PT thin film show a broad maximum near 35 °C, and an anomaly at the depolarizing temperature Td = 18 °C on heating only, suggesting a dipolar glass-relaxor phase transition. No structural phase transition at 18 °C is apparent from ferroelectric hysteresis loops taken on field cooling and field heating. These loops show the thermal hysteresis expected for ferroelectric relaxors, which has not hitherto been experimentally verified in PbMg2/3Nb1/3O3-PbTiO3 thin films. Our data suggest the intriguing possibility of a giant electrocaloric effect (ΔT = 9 K, ΔE = 720 kV cm−1) at and near room temperature.